Extra-Cerebellar Signs and Non-motor Features in Chinese Patients With Spinocerebellar Ataxia Type 3 - Yuan, Xiaoqin; Ou, Ruwei; Hou, Yanbing; Chen, Xueping; Cao, Bei; Hu, Xun; Shang, Huifang (Frontiers in Neurology, 2019)
Objectives: Our study attempted to systematically explore the prevalence of extra-cerebellar signs and non-motor symptoms, such as anxiety, depression, fatigue, excessive daytime sleepiness (EDS) and sleep disturbances in a cohort of Chinese patients with spinocerebellar ataxia type 3 (SCA3), and further investigated the correlations between non-motor symptoms and clinical characteristics in SCA3 patients. Methods: This study included 68 molecular-proven SCA3 patients. Extra-cerebellar signs were evaluated with the Inventory of Non-Ataxia Symptoms (INAS). The INAS count indicated the number of non-ataxia signs in each patient. The severity of ataxia, fatigue, EDS, sleep quality, anxiety, and depression were assessed using the Scale for the assessment and rating of ataxia (SARA), Fatigue Severity Scale (FSS), Epworth Sleepiness Scale (ESS), Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Rating Scale (HAMA), and the Hamilton Depression Rating Scale (HAMD) (24 items), respectively. Results: Extra-cerebellar signs were detected in 91.2% of all SCA3 patients and the mean total INAS count was 2.72 ± 1.88. Rigidity was the most frequent extra-cerebellar sign (47.1%, N = 32). Sensory symptoms (2.9%, N = 2) and chorea (5.9%, N = 4) were rare, and myoclonus (0%) was not found in this cohort. High frequencies of sleep disturbances (64.7%), fatigue (52.9%), depression (48.5%), and anxiety (42.6%) were detected in SCA3 patients. The Spearman correlation indicated that the HAMD score was associated with the CAG repeat length and HAMA score, while the PSQI score was correlated with the SARA and FSS score. In addition, multivariate linear regression analysis showed that the CAG repeat length, age of onset, sleep disturbances and depression were significant predictors of fatigue in SCA3 patients. Conclusions: Our study indicates that the vast majority of SCA3 patients display extra-cerebellar signs. Except for EDS, anxiety, depression, fatigue and impaired sleep quality are present in SCA3 patients. The CAG repeat length, age of onset, sleep disturbances and depression are predictors of fatigue in SCA3 patients.